Could parental awareness of DBR influence youth off-campus sports? Test of a conditional process model - Shuying Tan; Hu Lou; Xue Liu; Jin Chen (BMC, 2023)
Abstract Background The "Double Reduction" policy published in China provides a new opportunity to increase youth sports. Based on the perspective of parents' influence on their children, this study aimed to explore the impact of parental awareness of the "Double Reduction" policy on youth off-campus sports. Methods This study was conducted empirically through a nationwide sample survey to analyze the relationship between parental awareness of the "Double Reduction" policy, parental education anxiety, and parental attitudes toward children's participation in sports and youth off-campus sports to construct and verify a conditional process model. Results Parental awareness of the "Double Reduction" policy had a significant positive impact on their children's off-campus sports (β = 0.103, SE = 0.018, P < 0.01), but had a significant negative impact on parental education anxiety (β = -0.305, SE = 0.032, P < 0.01) which showed a significant negative effect on their children's off-campus sports (β = -0.114, SE = 0.011, P < 0.01) and played a significant intermediary role between parental awareness of the "Double Reduction" policy and children's off-campus sports (β = 0.031, 95%CI: 0.020 ~ 0.044). All dimensions of parental education anxiety showed different characteristics with only academic achievement anxiety (β = 0.034, 95%CI: 0.021 ~ 0.047), parent-child interaction anxiety (β = 0.027, 95%CI: 0.014 ~ 0.038), and learning attitude anxiety (β = 0.024, 95%CI: 0.015 ~ 0.033) presenting significant mediating effects. The interaction between parental education anxiety and parental attitudes toward children's sports significantly positively impacted youth off-campus sports (β = 0.008, SE = 0.001, P < 0.01). The moderating role of parental attitudes toward their children's participation in off-campus sports, indicating it was significant (95%CI: 0.005 ~ 0.011) along the pathway of parental awareness of the "Double Reduction" policy to parental education anxiety to youth off-campus sports. Conclusions Parental awareness of the "Double Reduction" policy has a positive impact on youth off-campus sports. Parents' anxiety about their children's academic achievement, parent-child interaction anxiety, and learning attitude anxiety mediate in the process model. Parental attitudes toward sports can magnify the relationship between their education anxiety and youth off-campus sports.